“CAROTID INTIMA MEDIA THICKNESS - A PREDICTOR OF CORONARY ARTERY DISEASE: RETROSPECTIVE ANALYSIS” - DR. ASHISH SINGHAL*, DR. SURBHI GUPTA, DR. ANKUR SINGHAL, DR. AASHIMA ARON (Innovative Journal of Medical and Health Sciences, 2020)
BACKGROUND Carotid artery intima-media thickness (CIMT) measurement is a non-invasive method to diagnose early atherosclerosis or predict the risk of myocardial infarction and stroke. Increased CIMT in the common carotid segment is accompanied by yearly risk of 0.7%– 2.2% in coronary heart disease, 0.4%–1.8% for stroke and from 1.8% to 3.2% for total cardiovascular disease. The aim of the study is to find the individual predictor role of CIMT in CAD (Coronary artery disease) patients. 100 Cases selected from CAD patients who underwent PTCA and 100 Controls selected with no history of CAD and stroke. CIMT measurements done in all at common carotid artery level. RESULTS Baseline characteristics like mean age, male sex, obesity, dyslipidemia, diabetes, hypertension, smoking and family history were comparable in cases and controls. The mean CIMT was 1.11 mm in the case and 0.87mm in control (P<0.0001). ROC analysis gave us a got optimal cut-off value of 1.0 mm above for which sensitivity, specificity, and positive and negative predictive values for predicting CAD was 73%, 73%, 73%, and 73%, respectively. Linear regression analysis showed a significant correlation between CIMT and presence of CAD with the R = 0.582 (P 0.001). Multiple logistic regression analysis showed only CIMT correlated (coefficient 8.03) significantly with presence of CAD. CONCLUSION CIMT independently can predict presence of CAD whether traditional atherosclerotic risk factors are present or not. Deploying CIMT evaluation in low and intermediate risk individual(s) to detect subclinical CAD will be a good strategy in resource limited setting specially where invasive modalities are not easily available. Key words: CIMT–CAD